Implementasi Pembelajaran Berbasis Budaya Lokal Minangkabau Pada Proyek Alek Pacu Jawi Di PAUD Al-Fa’izin - Ajat, Ajat; Emelda, Emelda; Robby, Robby; Haryani, Yeni; Eliyanah, Eliyanah; Hafid, Perawati (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2024)
This research aims to reveal the implementation of learning based on local Minangkabau culture Alek Pacu Jawi in Early Childhood Education at Al-Fa'izin PAUD Tanah Datar Regency. With this local culture-based learning, it is hoped that children can understand from an early age the noble Minangkabau values of Alek Pacu Jawi in Tanah Datar Regency. Researchers conducted direct observations and interviews at PAUD Al-Fa’izin Nagari Sawah Tangah, Pariangan District, Tanah Datar Regency. In this case the researcher chooses the right informant to obtain more accurate information. The potential of the surrounding environment is a learning resource used by PAUD Al-Fa’izin in the form of the potential of nature, culture and the surrounding community which can stimulate children's curiosity. The preparation of this local culture-based learning is based on the experience of Al-Fa'izin PAUD during its time as a pilot for the Inquiry Village Program in Tanah Datar Regency based on the elements needed in managing learning which are then integrated with the need for the introduction of local culture in early childhood in order to introduce culture and foster children's character and love of local culture.